Evaluation of Healthy Lifestyle Behaviours of Faculty Members - Şenbakar , Kubilay (Progress in Nutrition, 2021)
The aim of this study is to evaluate the healthy lifestyle behaviours of the faculty members. Population of the research is consisted of the faculty members in Fırat University in Elazığ province. Its sample is consisted of 150 faculty members randomly selected among the faculty members. In our study, the validity of the scale developed by Walker et al. (1987) and subsequently revised (1996), in Turkey was done by Bahar et al. (2008). Accordingly, sub-dimensions of SYBD (Healthy Lifestyle Behaviours) consisted of 52 questions and come under 6 dimensions are as follows: Spiritual development, health responsibility, physical activity, nutrition, interpersonal relationships, and stress management. All questions regarding SYBD are never calculated by likert scale such as never (1), sometimes (2), often (3), regularly (4). In the analysis of data in the study and the calculation of results obtained, SPSS 22,0 statistical program was used. The significance level was determined as P